2010
DOI: 10.1111/j.1468-5957.2010.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

UK IPOs: Long Run Returns, Behavioural Timing and Pseudo Timing

Abstract: Abstract:In this paper we examine a comprehensive set of 2,499 UK IPOs launched between mid-1975 and the end of 2004. We find compelling evidence of long run under-performance that persists for between 36 and 60 months post-flotation, depending on the precise method chosen to measure abnormal returns. Following Schultz (2003), we ask whether our results are consistent with 'pseudo-timing'. Equally-weighted returns in calendar time provide further evidence of under-performance, a result that favours the Loughra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 39 publications
(100 reference statements)
3
47
0
Order By: Relevance
“…Turning to the results themselves, Table 6 presents the results for the GLS model of Gregory et al (2010). Overall, and in line with previous findings on UK cash takeovers, alphas are slightly negative but not significantly different from zero.…”
supporting
confidence: 78%
“…Turning to the results themselves, Table 6 presents the results for the GLS model of Gregory et al (2010). Overall, and in line with previous findings on UK cash takeovers, alphas are slightly negative but not significantly different from zero.…”
supporting
confidence: 78%
“…This compares to the negative stock-returns found for U.S., U.K. and the Netherlands. Espenlaub et al (2000) report 3-year stock price performance of -8% to -28% for U.K. IPOs, likewise Gregory et al (2010) report 3-year stock price performance of -12.6% for U.K. IPOs, Roosenboom et al (2003) report underperformance of -13% to -30% for Deutch IPOs and Ritter (1991) reports underperformance of -16.67% over the first 3 years for U.S. IPOs. Consistent with the third hypothesis, the long-run underperformance of IPOs is largely centered in the toptier group of 35 IPO firms with the highest use of DCA in the IPO year (Mann-Whitney U test, p-value = 0.025).…”
Section: Univariate Analysismentioning
confidence: 99%
“…The final sample consists of 3054 IPOs (excluding privatizations). This study uses large data set of UK IPOs, compared to prior studies on UK IPOs, such as Loughran et al (1994), Gerbich (1996), Michailides (2000) and Gregory et al (2010). Loughran et al"s (1994) [1998][1999][2000][2001][2002][2003][2004][2005][2006][2007].…”
Section: Datamentioning
confidence: 99%
“…Indeed, some of these hypotheses have been tested before in several studies in the UK context, yet these studies have examined only different subsets of these theories, with financial modelling subject to several econometric critiques. In specific, the UK IPOs activity in the context of timing has been examined by Loughran, Ritter, and Rydqvist (1994), Gerbich (1996), Rees (1997), Michailides (2000) and Gregory, Guermat and Al-Shawawreh (2010), whilst the timing of UK rights issues has been only examined by Michailides (2000) (Note 1). On the other hand, modeling the IPOs and rights issues, as a time-series count variable, empirically poses a number of econometric difficulties, so any modeling attempts should account for these econometric considerations (Ljungqvist, 1995), yet none of the UK-based studies are found to provide an adequate modeling that simultaneously incorporates both the time-series and statistical properties of the IPOs and rights issues variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation